EFEKTIVITAS PENERAPAN REHABILITASI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DI INDONESIA - Riyadi, Trisno; Chandra, Tofik Yanuar; Paparang, Santrawan T. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Narcotics crime is an extraordinary offense that has serious impacts on individuals, society, and the state. In its handling, there has been a paradigm shift from repressive approaches to rehabilitative ones, particularly for addicts or narcotics abusers. This study aims to analyze the effectiveness of the rehabilitation implementation for narcotics crime perpetrators in Indonesia, based on the current legal framework, particularly by comparing the old Penal Code (Law No. 1 of 1946) with the new National Penal Code (Law No. 1 of 2023), as well as Law No. 35 of 2009 concerning Narcotics. This research adopts a normative juridical method with statutory, case, conceptual, and analytical approaches. The data were obtained from primary, secondary, and tertiary legal materials and analyzed using legal interpretation and legal construction methods. The study examines the types of rehabilitation applied in Indonesia, both medical and social, including case studies such as the decisions involving Tri Retno Prayudati (Nunung) and Reza Pardede (Coki Pardede), which demonstrate the varied application of rehabilitation among similar offenders. The main findings reveal that although rehabilitation is formally accommodated in national regulations, its implementation remains suboptimal. Obstacles such as inconsistent understanding among law enforcement officers, limited rehabilitation facilities, and the lack of clear parameters to distinguish users from dealers hinder effective enforcement. The disparity in treatment among narcotics offenders remains high, as illustrated by the case of Nunu Nurhayati, who received a prison sentence without rehabilitation. This study applies restorative justice theories from Howard Zehr and Tony Marshall, emphasizing the restoration of social relationships and individual recovery over punishment, as well as effectiveness theories from Soerjono Soekanto and Lawrence M. Friedman to evaluate the legal policy's effectiveness. The study concludes that applying rehabilitation to narcotics offenders is more in line with the principles of restorative justice and human rights protection. Therefore, the state needs to strengthen the legal foundation and technical implementation of rehabilitation and shift the paradigm among law enforcers and society to view addicts not as criminals, but as individuals in need of recovery.